Investigation of Variable Amplitude Loading and Stress Ratio in the Very High Cycle Fatigue Regime Using Micro-notched Specimens. (2015) - Müller, Thomas; Sander, Manuela
Abstract: In order to study the effect of small defects in the regime of very high cycle fatigue, 20 μm deep micro-notches are introduced into the specimens by laser sublimation. Tests are performed using an ultrasonic fatigue testing system. For the variable amplitude loading tests a reconstructed load sequence on the basis of a standardized load time history called FELIX is used and transformed to the stress ratios of -1 and 0. The experimental results are compared to previous investigations with smooth specimens. Moreover, calculated Gassner lines using the linear damage accumulation are compared to the experimental results.